1995
DOI: 10.1007/bf01565479
|View full text |Cite
|
Sign up to set email alerts
|

Fire during arthroscopy — an unusual complication

Abstract: We report a case of fire during routine arthroscopy. This is an unusual but potentially disastrous complication. Recommendations are presented for preventing such an event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This database review reported 4 events of fires during arthroscopic procedures; however, all were attributed to the electrocautery devices used. On review of the literature, a case report stated that a fire occurred after an arthroscopic light source was unattached while lying on the drapes 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This database review reported 4 events of fires during arthroscopic procedures; however, all were attributed to the electrocautery devices used. On review of the literature, a case report stated that a fire occurred after an arthroscopic light source was unattached while lying on the drapes 26 .…”
Section: Discussionmentioning
confidence: 99%